MACHIAVELLIANISM TRAIT AMONG MALAYSIAN YOUNG ADULTS: AVOIDANT ATTACHMENT TENDENCIES AND PERCEPTION OF TRUST TOWARDS CLOSE FRIENDS AND ACQUAINTANCES - Ling, Kristy Chong Yi; Ng, Joo Hou (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This quantitative study aims to further explore individuals’ perception of trust within the Malaysian young adults’ context. Trust is measured based on two components: close friends and acquaintances. Individual differences are examined based on the Machiavellianism trait (i.e., low, neutral and high Machiavellianism) and the avoidant attachment styles (i.e., dismissive-avoidant, and fearful-avoidant attachment styles). 290 participants aged between 18 to 39 years old were recruited to complete an online survey. Correlation and one-way ANOVA(s) were conducted to analyse the data obtained. The present study found significant differences among those with low, neutral, and high Machiavellianism trait regarding their perception of trust specifically towards close friends. The Machiavellianism trait is also a negative predictor upon trust towards close friends. However, trust towards acquaintances is only marginally significant on each Machiavellianism level hence this relationship should be further explored in future studies. On the other hand, individuals with higher avoidant tendencies self-reported lower trust towards others regardless of their relationship (i.e., close friends versus acquaintances). The avoidant attachment styles are also negative predictors upon trust towards close friends. This study can serve as a reference for professional counsellors in assisting their clients in building trust. Limitations and future research are discussed.